More-Than-Human: A Cross-Sectional Study Exploring Children’s Perceptions of Health and Health-Promoting Neighbourhoods in Aotearoa New Zealand - Williams, T; Ward, K; Egli, V; Mandic, S; Pocock, T; Clark, TC; Smith, M (MDPI AG, 2022)
A disconnect between children’s ideas and their incorporation into environmental design, in the context of rapid urbanisation and climate crises, compelled us to reflect on children’s meaningful participation in positive environmental change. Our research aimed to bring new knowledge to the fore using a participatory, child-centred approach to understanding children’s perceptions of health and health-promoting neighbourhoods in Aotearoa New Zealand. The cross-sectional Neighbourhoods and Health study was conducted with 93 primary school-aged children (approximate ages 8 to 10 years) from two schools in Ōtepoti Dunedin and two schools in Tāmaki Makaurau Auckland from June 2020 to August 2021. We present a framework of twelve child-centred topics of importance for health (Healthcare and ‘not getting sick’, ‘How you feel’, and Taking care of yourself), health-promoting neighbourhoods (Proximity, safety and feel, Range of ‘places to go’, ‘Friendly streets’, and ‘No smoking’), and those common to both (Connections with other humans, Healthy food and drink, Exercising and playing sport ‘to keep fit’, ‘Nature’ and ‘helping the environment’, and Recreational activities). The more-than-human theory was used to situate our study findings, and we explored three threads evident in children’s thinking: (1) care for humans and non-humans, (2) vital interdependence of human–non-human relations, and (3) understanding complex urban environments through everyday activities. We conclude that the thriving of humans and non-humans in urban environments is important to children in Aotearoa New Zealand. We affirm that children have clear and salient ideas about health and health-promoting neighbourhoods.
Keywords: child wellbeing; child-friendly cities; participatory approaches; posthuman; public health; urban design; 4203 Health Services and Systems; 4206 Public Health; 42 Health Sciences; 44 Human Society; 4406 Human Geography; Pediatric; Generic health relevance; 3 Good Health and Well Being; Toxicology; Humans; Child; Cross-Sectional Studies; New Zealand; Exercise; Schools; Sports; Humans; Exercise; Cross-Sectional Studies; Schools; Sports; Child; New Zealand; Humans; Child; Cross-Sectional Studies; New Zealand; Exercise; Schools; Sports